1997
DOI: 10.1097/00004836-199707000-00006
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Celiac Sprue among Patients with Primary Biliary Cirrhosis

Abstract: Although coexisting primary biliary cirrhosis (PBC) and celiac sprue have been described, celiac sprue is sufficiently common in western Europe for chance to explain isolated cases. We screened our patients with PBC for celiac sprue using serum immunoglobulin A endomysial antibody (EmA), with confirmation by duodenal biopsy in EmA-positive patients. Of 57 patients, 6 (11%) had EmA. Four agreed to have a biopsy taken, and all had villous atrophy, yielding a minimum prevalence of 1:14 (7%). Apart from anemia in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 17 publications
1
43
1
3
Order By: Relevance
“…Furthermore, the association between CD and autoimmune liver diseases is also a matter of debate (9,11,17,19,23,40,41,43,47,48). Several studies reported a firm link of CD with autoimmune cholestatic liver diseases, recommending screening for CD of patients with these disorders and vice versa (screening for PBC and/or PSC in patients with CD) (11,17,19,23,41,48).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the association between CD and autoimmune liver diseases is also a matter of debate (9,11,17,19,23,40,41,43,47,48). Several studies reported a firm link of CD with autoimmune cholestatic liver diseases, recommending screening for CD of patients with these disorders and vice versa (screening for PBC and/or PSC in patients with CD) (11,17,19,23,41,48).…”
Section: Discussionmentioning
confidence: 99%
“…Liver blood tests did not improve in patients with silent CD and PBC after 12 to 24 months on a GFD despite the disappearance of the endomysial antibody in the serum. 30 Information regarding the stage of PBC in these patients, however, was not provided. 30 Pruritus and cholestasis did not improve after 12 months of gluten withdrawal in cases with PBC and severe liver disease [stage IV on histology (Scheuer's classification), with ALP elevations 3.1-4.8 times the upper limit of normal].…”
Section: Primary Biliary Cirrhosismentioning
confidence: 99%
“…30 Information regarding the stage of PBC in these patients, however, was not provided. 30 Pruritus and cholestasis did not improve after 12 months of gluten withdrawal in cases with PBC and severe liver disease [stage IV on histology (Scheuer's classification), with ALP elevations 3.1-4.8 times the upper limit of normal]. These patients also were treated with ursodeoxycholic acid.…”
Section: Primary Biliary Cirrhosismentioning
confidence: 99%
See 1 more Smart Citation
“…Among the complications related to celiac disease, many are worsened if the patient consumes in excess alcoholic beverages, for example, peripheral neuropathy (14,15) and epilepsy (16). Abnormal levels of aminotransferases (17) can be found in patients with celiac disease, as well as an association with several autoimmune chronic liver diseases such as primary biliary cirrhosis (18,19). There is also an increased risk of autoimmune cardiomyopathy (20,21).…”
Section: Introductionmentioning
confidence: 99%